Factors Associated With Uptake of Breast Cancer Screening Among Catholic Nuns in Lake Zone, Tanzania - Gotfrida Marandu; Rose Laisser; Kija Malale; Peter Rambau (International Journal of Breast Cancer)
Conclusion: A study found a low uptake of breast cancer screening among Catholic nuns. This highlights the need for breast health intervention programs within religious congregations to address misconceptions and promote early detection.